Evaluation of RNA Extraction-Free Method for Detection of SARS-CoV-2 in Salivary Samples for Mass Screening for COVID-19. (30th June 2021) - Mahmoud, Sally A.; Ganesan, Subhashini; Ibrahim, Esra; Thakre, Bhagyashree; Teddy, Juliet G.; Raheja, Preety; Abbas, Walid Z.
Abstract : In this COVID-19 pandemic, there is a dire need for cost-effective and less time-consuming alternatives for SARS-CoV-2 testing. The RNA extraction-free method for detecting SARS-CoV-2 in saliva is a promising option. This study found that it has high sensitivity (85.34%), specificity (95.04%), and was comparable to the gold standard nasopharyngeal swab (NPS) sample tests. The method showed good agreement between salivary and NPS samples, with a kappa coefficient of 0.797. However, there are variations in the sensitivity and specificity based on the RT-PCR kit used. The Thermo Fisher Applied Biosystems showed high sensitivity, positive predictive value (PPV), and negative predictive value (NPV) but also showed a higher percentage of invalid reports. On the other hand, the BGI kit showed high specificity, better agreement (kappa coefficient) between the results of saliva and NPS samples, and higher correlation between the Ct values of saliva and NPS samples. Thus, the RNA extraction-free method for salivary sample serves as an effective alternative screening method for COVID-19.